Strengthening the Role of the Family in the Revitalization of the Biak Language in Dwar Village - Smas, Musa Hefer; Handayani, Tri; Mokay, Meggy Merlin (Yayasan Daarul Huda Kruengmane, 2026)
The revitalization of regional languages is a strategic effort to preserve the continuity of cultural identity amid globalization. The Biak language, as one of the regional languages in Papua, has experienced a decline in usage, particularly among the younger generation, due to the dominance of the Indonesian language in daily communication. This community service activity aims to strengthen the role of the family as the primary agent in the revitalization of the Biak language through a participatory and contextual mentoring approach in Dwar Village. The implementation method includes stages of problem identification, socialization, training, family mentoring, and evaluation. The results of the activity indicate improvements in the cognitive, affective, and psychomotor aspects of participants, as evidenced by increased understanding, changes in attitudes, and enhanced language skills among children. In addition, a habit of using the Biak language within the family environment has been established as a form of language internalization in daily life. These findings confirm that the family plays a strategic role in intergenerational language transmission. Therefore, a family-based mentoring approach has proven effective as a sustainable model for regional language revitalization and has the potential to be replicated in other communities with similar characteristics.